2021
DOI: 10.1002/lary.29870
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Adjuvant Therapy After Surgery for Oropharyngeal Squamous Cell Carcinoma

Abstract: Objectives/Hypothesis: We aim to 1) evaluate trends in adjuvant treatment of human papilloma virus (HPV)-related oropharyngeal cancer; 2) assess change in complications and functional outcomes over time; and 3) assess change in overall and disease-free survival (DFS) over time.Study Design: Retrospective analysis. Methods: Charts of patients who underwent transoral robotic surgery for HPV-related oropharyngeal cancer between 2011 and 2019 were reviewed. Trend analysis was used to compare rate of adjuvant treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The title and abstract assessment yielded 79 studies to be obtained in a full-text version. According to the abovementioned eligibility criteria, 22 studies [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] were included in this review, and a total of 3992 patients treated with upfront TORS were identified, with a median age of 59.5 (IQR 57.9–61.0). The reasons for the exclusion of the other studies are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The title and abstract assessment yielded 79 studies to be obtained in a full-text version. According to the abovementioned eligibility criteria, 22 studies [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] were included in this review, and a total of 3992 patients treated with upfront TORS were identified, with a median age of 59.5 (IQR 57.9–61.0). The reasons for the exclusion of the other studies are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%